Recorte de gênero, problemas de voz e faltas dos professores ao trabalho nas Escolas da Educação Básica no Brasil - Luciana Daniella Lages (2017)
Introduction: Among the morbidities associated with teaching activity are the voice problems which can cause limitations in work performance and keep the teacher away from the classrooms. The literature shows the relevance of these problems in this category and points out differences in the prevalence between men and women. Objectives: To verify the scientific production in the last ten years about the frequency and factors associated with absences from work due to voice problems and to describe differences between teachers of Basic Education in Brazil who have left work for this reason. Methods: Bibliographic review of articles from 2005 to 2015 and a cross-sectional study with stratified sample selected by simple random selection of Brazilian Basic Education teachers. Data collection was performed between October 2015 and March 2016 through telephone interviews. Descriptive analysis with numerical synthesis and percentage and chi-square test were performed for verifying associations with gender. Results: In the literature review 15 cross-sectional and quantitative studies articles were found. The frequency of teacher absences due to voice problems ranged from 7 to 63%. Factors associated with these faults were: female gender, vocal complaint during professional training, reports of violence, depression or anxiety, respiratory problems, negative impact and severity of voice disorders in the teacher's life. Field survey results showed that among teachers who missed work because of voice problems (n=1039) 328 were men (31.9%) and 701 women (68.1%). Considering age, those aged up to 44 years (66.4% women and 75.1% men) have predominated. Most of the missing teachers had companions and one or more children. There was no difference statistically significant in gender. In relation to the number of children younger than 10 yearsold, the proportion of men was higher (39.7% vs 29.6%, p = 0.005). However, they eported to have performed household tasks less frequently than women did (40.9% vs. 72,0%, p <0.001). The proportion of men having workload up to 40 hours per week (35.2% vs 28.7% p = 0.013) was higher than the womens. The number of male teachers who reported to work in more than one school (63.6% vs 55.3% p = 0.016),was higher. This group has also reported to have another professional activity in a different sector (19.3% vs. 7.8% p <0.001), and to receivei more than three minimum wages in the selected school (41.3% vs 30.1% p = 0.001). The results have shown association between the absences of male and female teachers, and teachers' voice problems for the variables: age group, frequency of household tasks, number of children under 10 years old, to work in another school, total weekly hours of work in schools, to work in another sector and remuneration. Conclusion: There is a considerable increase in scientific publications on the subject, but there are still gaps in the prevalence of work-related absences due to voice problems and associated factors. The absences for these problems affect mainly the female teachers. There was a statistically significant difference among teachers regarding sociodemographic, work and employment aspects. Male teachers who moved away from their teaching activities because of their voice presented characteristics of personal and working life distinct from the teachers. The configurations of masculine and feminine identities influence the division of labor between male and female teacher indicate the contribution of gender issues in illness and the decision to absent from work due to voice problem.